The impact of in-cylinder charge motion on lean limit extension and in-pre-chamber mixture preparation in a homogeneous ultra-lean engine - Bunce, Michael P. (2022)
The perpetual desire to conserve fuel is driving strong demand for increased efficiency in spark ignited (SI) engines. A method being increasingly explored to accomplish this goal is lean combustion. Homogeneous ultra-lean combustion with λ > 1.6 has demonstrated the ability to both increase thermal efficiency and significantly reduce engine-out nitrogen oxides (NOx) emissions due to the colder cylinder temperatures innate to combustion with high levels of dilution. The major limitation in developing lean and ultra-lean combustion systems is the less favorable ignition quality of the mixture. This has necessitated the development of higher energy ignition sources. A pre-chamber combustor application known as jet ignition is one such technology, having been researched extensively. Differing types and magnitudes of charge motion are incorporated in SI engines to aid with mixture preparation. The influence of charge motion over lean SI combustion however is less well understood. Additionally, charge motion introduced in the main combustion chamber has the potential to translate to the pre-chamber, thereby affecting pre-chamber mixing and combustion. The effect of charge motion on mixing and combustion comprehensively throughout the engine cycle is unknown and has not been investigated. This study seeks to evaluate the impact of charge motion on mixture preparation and combustion processes in a jet ignition engine. Experimental engine testing is undertaken to quantify the impact of differing levels and types of induced charge motion on pre-chamber and main chamber combustion. An analysis of high speed pressure data from the pre-chamber provides insight into how charge motion affects pre-chamber combustion stability, and how instabilities cascade to the main chamber combustion event. A set of simulations, matched to experimental engine results, is used to develop an understanding of charge motion influence over the complexities of in-pre-chamber phenomena that are not easily observed experimentally. From the synthesis of these data sets, a clear understanding of the role that charge motion plays in homogeneous highly dilute jet ignition engines emerges. This study quantifies the impact that charge motion has on lean limit extension and engine efficiency, identifies optimal charge motion type, and provides a roadmap for engine system optimization.